2018
DOI: 10.1002/cctc.201701910
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel Entrapped Nitroxyl Radicals: Catalysts of Broad Scope

Abstract: Sol–gel entrapped TEMPO‐like radicals are excellent supported molecular catalysts for the selective and clean alcohol oxidation, including the primary hydroxyl functions of cellulose. Could these materials reach widespread utilization for the synthesis of fine chemicals, bio‐based building blocks and even carboxyl cellulose nanofibrils? This study offers a critical perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Silica-supported TEMPO organic− inorganic hybrid materials are commonly used as heterogeneous catalysts. 21 One of the most common supports used for heterogeneous TEMPO catalysts is mesoporous silica. On the other hand, amorphous silica is sometimes used because of its high surface area and low cost, but the irregularity of the surface and pore structure can be detrimental in some applications.…”
Section: Tempo Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica-supported TEMPO organic− inorganic hybrid materials are commonly used as heterogeneous catalysts. 21 One of the most common supports used for heterogeneous TEMPO catalysts is mesoporous silica. On the other hand, amorphous silica is sometimes used because of its high surface area and low cost, but the irregularity of the surface and pore structure can be detrimental in some applications.…”
Section: Tempo Immobilizationmentioning
confidence: 99%
“…Inorganic sol−gel supports for TEMPO derivatives are indeed superior in their thermal stability, inertness, protectability toward entrapped molecules, as well as their porosity and high surface areas. 21 In the most recent review by Megiel, 15 some of the earlier reports on heterogeneous TEMPO catalysts immobilized on various silicas, including ultrafine silica particles, 28 commercial aminopropyl-functionalized silica, 29 sol−gel silica, 30,31 32 and SBA-15, 33 have been well summarized. These heterogeneous TEMPO powder catalysts were applied for alcohol oxidation and were readily recovered from the reaction mixture by centrifugation, which facilitated their convenient recycling and reuse.…”
Section: Tempo Immobilizationmentioning
confidence: 99%
“…An interesting direction would be to explore entrapped/supported molecular catalysts, which, for example, showed a good performance in the selective and clean alcohol oxidation. 239 A recent trend has shown that HMF is often used as a challenging substrate to test new catalysts developed for reduction or oxidation processes. Indeed, biomass processing provides a strong driving force and acts as a "grindstone" for sharpening new catalytic systems.…”
Section: Discussionmentioning
confidence: 99%
“…and reductants (H 2 , regenerable reductants, etc.). An interesting direction would be to explore entrapped/supported molecular catalysts, which, for example, showed a good performance in the selective and clean alcohol oxidation …”
Section: Conclusion and Perspectivesmentioning
confidence: 99%
“…A number of researchers have studied TEMPO immobilized on solid supports, such as polystyrene-bound TEMPO (PS-TEMPO) [12], FibreCat TEMPO [13], TurboBeads-TEMPO (TEMPO immobilized on the outer surface of Fe 3 O 4 magnetic nanoparticles) [14], and organosilica xerogel (SiliaCat TEMPO) [15,16]. While these types of heterogeneous TEMPO catalyst clouds have been applied to the conversion of molecular chemicals, their use in the form of structured polymers, such as cellulose nanofibers, has been limited due to the steric hindrance between the solid supports and the nanofibers.…”
Section: Introductionmentioning
confidence: 99%